Flooding Schools: School Mental Health Providers and the Climate Crisis - Erik J. Reinbergs; Sarah Fefer (International Journal of School Social Work, 2020)
This study provides an example of using a problem-solving model to explore the impact of the climate crisis on schools. Using publicly available climate change and flooding prediction data, we estimate that by 2100, assuming a “medium” climate change scenario, more than 1677 schools in the coastal United States are expected to flood every year and more than 2262 schools are expected to flood every 10 years. Within the data, “medium” is defined as warming levels that will lead to an estimated five feet of sea level rise by the year 2100. Limitations in the data suggest these numbers are likely overly conservative estimates and preclude the analysis of more extreme climate models. Potential actions, the role school mental health providers, and the involvement of students in climate advocacy are discussed.
Keywords: crisis response; crisis preparedness; climate change; advocacy